Effectiveness of travel behavior and infrastructure change to mitigate heat exposure - Li, Rui; Chester, Mikhail V.; Middel, Ariane; Vanos, Jennifer K.; Hernandez-Cortes, Danae; Buo, Isaac; Hondula, David M. (Frontiers in Sustainable Cities, 2023)
Urban heat exposure is an increasing health risk among urban dwellers. Many cities are considering accommodating active mobility, especially walking and biking, to reduce urban-induced anthropogenic greenhouse gas (GHG) emissions. However, promoting active mobility without proper planning and transportation infrastructure to combat extreme heat exposure may cause more heat-related morbidity and mortality in the climate change future. This study estimated the effectiveness of active trip heat exposure mitigation under built environment and travel behavior change. Simulations of the Phoenix metro region's 624,987 active trips were conducted using the Activity-based travel model (ABM), simulated Mean Radiant Temperature (TMRT), transportation network, Local Climate Zones, and supplemental data. Two cooling scenarios were designed to identify the cool corridors with the low-temperature and represent different built environment cooling levels. Travelers experienced TMRT heat exposure ranging from 29°C to 76°C (84°F to 168°F) on the simulation day. In the same cooling scenario, behavior changing cooled up to ten times more trips than the built environment changing. Active trips reduced an average of 1.2°C to 3.7°C based on different scenarios when the networks were fully converted to the cool corridors. The marginal benefit of the cooling decreased from over 1,000 trips/km when less than 10 km of corridors were converted to less than 1 trip/km when all corridors were transformed. The results revealed that heavily traveled corridors should be prioritized with limited resources, and the best cooling results come from environment and travel behavior change together. This study confirmed prior efforts in personal heat exposure studies that individual-level heat exposure provides more precise insights into how people are exposed to heat.